سعد محمد صالح عبد الصمد بعض الملاحظات حول عمر ونمو سمكة الشانك latus (Houttuyn) Acanthopagrus في نهر شط العرب - محمدسعد (University of Thi-Qar Journal of Science, 2019)
A 263 specimens of Acanthopagrus latus were collected from Shatt Al-Arab river from October 2008 to March 2009 to study age and growth of this species. The results revealed that length(L)weight(W) relationship was log W=-4.8512+3.0452 logTL , the length(L)- scale radius(S) related as : L=58.69+26.295S and Von Bertalanffy equation was Lt = 370.59(1-e 67 -0.1993(t+2.7518) ) .